It’s Never Too Late to Start Again: Examining Levels of Engagement of Female Students in a Rural Vocational Program - Solarz, Stephanie (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
This qualitative phenomenological study describes the experiences of female students in a rural Alberta vocational training centre through semi-structured interviews. The findings indicate five key ways that instructors and institutions can approach instruction to maximize the opportunity for early and sustained student engagement: a sense of belonging and feeling of community, relationships with instructors, consistent and clear organization and structure, the recognition of student success, and the opportunity to explore new skills and careers.